The Use of English in Housing Names in Banyumas Regency: A Review of Language Policy in Indonesia - Chusni Hadiati; Eni Nur Aeni; Rizki Februansyah (Jurnal Lingua Idea, 2021)
Language policy in Indonesia have not completely indicated the dignity of Bahasa Indonesia as the national language of Indonesia. One reason why this phenomenon takes place is the lack of socialization of Bahasa Indonesia in public space. The use of English in Indonesian housing names indicates the violation to the position of Bahasa Indonesia as the national language. Despite the issue of Law No. 24/ 2009, the lack of socialization influences the use of English in Indonesian housing names. By using descriptive qualitative research and interview, this article enlightens the use of English in housing names related to the language policy. Analysis was done by identifying the policy released by the local government, developers’ consideration in creating a housing name and buyers’ consideration in choosing a house. This result shows that the use of English in Indonesian housing names are caused by the lack of socialization of the language policy. It suggests that the collaboration among the government, stakeholders and society is essential in preserving the language policy.